Effect of temporally modulated pulse on reducing recast layer in laser drilling. Issue 5 (November 2016) - Duan, Wenqiang; Dong, Xia; Wang, Kedian; Fan, Zhengjie; Mei, Xuesong; Wang, Wenjun; Lv, Jing
Abstract Temporally modulated-pulse laser is a promising technique; it has many advantages compared with normal pulse laser. The modulated pulse studied in this work was comprised of a wide pre-heating pulse front and a sharp pulse trail. The experiments were carried out mainly to study the influence of pre-heating subpulse energy and duration, while the trail subpulse was invariant. Both blind-hole and through-hole drillings were carried out, finding that there were some important differences between them. In blind-hole drillings, the deep melting caused by pre-heating subpulses greatly enhanced the absorptivity of laser energy of the sharp pulse trail, which increased the vaporization rate and pressure, and eventually expelled most of the liquid melt from the cave, leaving a very small quantity to resolidify as recast layer. In through-hole drillings, although the minimum recast layer thickness was reduced to 2.5 μm, the hole quality was found to be very sensitive to sample thickness. Once the pre-melting depth exceeds the sample thickness, it would be very difficult for the remnant pulses to expel the melt chunk. High-quality holes can only be drilled when the pre-melting depth is close to the back surface but melt through does not happen. Even so, the recast layer at the hole exit was always thicker than that at the other parts of the hole due to the sudden slump of recoil pressure when the hole was drilled through.